Analisis logika Fuzzy Sugeno dan Pengambilan Keputusan untuk meningkatkan produksi roti manis pada Tandi’s Homemade Bakery - Zerlinda, Frea Marva; Zaidan, Muhammad Zulfa; Akifah, Nur; Devrida, Safira Putri; Sinaga, Helsan Davidson (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Tandi’s Homemade Bakery, a small-medium enterprise, faces challenges in improving the quality and quantity of its sweet bread production, particularly in optimizing the production process and determining effective strategies. This study aims to analyze decision-making using the Fuzzy Sugeno Logic and Analytical Hierarchy Process methods as approaches to support production enhancement. The Fuzzy Sugeno method is applied to evaluate bread maturity levels based on parameters such as dough kneading time of 43 minutes, baking temperature of 173 degrees Celsius, and baking time of 60 minutes, with the goal of identifying optimal conditions to achieve high-quality bread. Meanwhile, the Analytical Hierarchy Process method is employed to establish alternative strategies for production improvement by analyzing criteria such as product quality, raw material efficiency, and operational costs. The findings suggest that integrating Fuzzy Sugeno and Analytical Hierarchy Process methods can provide structured planning recommendations, supporting Tandi’s Homemade Bakery in making informed decisions to enhance sweet bread production with superior quality.